Histopathological studies in canine transmissible venereal tumour - JAIN, ANITA; TIWARl, R P; TIWARI, S K; GUPTA, NEELU; AWASTHl, M K (The Indian Journal of Animal Reproduction, 2023)
Six dogs, naturally affected with Transmissible venereal Tumour (TVT) were treated with vincristinesulfate @ 0.025 mg/kg body weight intravenously (IN) at weekly interval for 5 weeks. The TVT affected tissueswere collected with Neilson biopsy punch on day O (before treatment) and on day 3 and 7, occasionally on day 14after treatment, Appreciable degenerative changes were observed in nuclei and cytoplasm of tumour cells after3rd day of treatment while after 7th day marked lymphocytic infiltration and increased amount of fibrous tissueswere seen along with appreciable reduction in tumour cells. The primary effect ofvincristine sulfate was on nucleiof TVT cells causing their condensation, karyorhexis and karyolysis. Present study confirmed that vincristinesulfate completely regressed the TVT in dogs.
Keywords: Canine venereal tumour; histopathology; vincristine sulphate